Chrysosporium queenslandicum: a potent keratinophilic fungus for keratinous waste degradation - Tarun Kumar Kumawat; Anima Sharma; Seema Bhadauria (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Keratinous wastes are the solid environmental pollutant generated from poultry farms, slaughterhouses and barber’s shops. The aim of the present study is the degradation of keratinous wastes in an eco-friendly way by biological methods, which should further be helpful to reduce the wastes and recycled into valuable feed and fertilizers. Methods Degradation of keratinous substrates was assessed by highly potent keratinophilic fungi, namely Chrysosporium queenslandicum TKKASb Apinis and R.G. Rees. This chicken feather degrading fungal strain previously isolated and identified by morphological and 18 s rDNA sequencing in laboratory, was used in the present study. Ch. queenslandicum was inoculated into the basal salt medium (BSM) with keratinous substrates for 12 and 24 days at 28 ± 2 °C to observe degradation. The rate of degradation was expressed as weight loss of keratin substrate over incubation days and pH variation. Results In this study, Ch. queenslandicum showed maximum degradation on chicken feathers followed by human nail clippings, animal hair and human hair. The degradation rate on chicken feather was 38.40 ± 0.80 and 46.40 ± 2.50% after 12 and 24 days, respectively. The basal salt medium’s pH was increased over incubation time. Scanning electron microscopy (SEM) examination also demonstrated the degradation of chicken feathers. Conclusions The results suggest that Ch. queenslandicum possess the potential biotechnological applications which can be used in the hydrolysis of keratinous waste and recycling of poultry waste for environmental protection. The hydrolyzed keratinous material can also be utilized as the source of fertilizers for plants and feed for animals.